Privát történelem . Private History - Bódy, Gábor; Tìmár, Péter (Hungary, 1978)
Experimental montage film that uses a selection of Hungarian home movies from before WWII, juxtaposed with contemporary popular music, radio programs and political speeches. An original representation of social history of Hungary through found footage.